The impact of gated communities on spatial transformation in the Greater Johannesburg area - Landman, Karina; Badenhorst, Willem (South African Research Chair in Development Planning and Modelling, School of Architecture and Planning,University of the Witwatersrand., 2012)
The main research question relates to the impact of gated communities on urban spatial transformation in the greater Johannesburg area. This translated into three objectives, namely: 1. To determine the extent of different types of gated communities in the City of Johannesburg. 2. To determine the impact of gated communities on spatial transformation in relation to processes of social, economic, environmental, institutional and political change. 3. To identify the implications for spatial restructuring and sustainable urban development in the City of Joburg.
Research Report